Studies On Accumulation Of Micronutrients Through Runoff In A Potable Water Resource, Bhopal (M.P.) - Ganesh Ram Namdev; Avinash Bajpai; Suman Malik (International Journal of Pharma and Bio Sciences, 2011)
Micronutrients play major role in determining the biological processes of a Lake ecosystem. The availability of micronutrients especially Zn , Cu, Mo and Mn in a water body is largely governed by the characteristics of its catchment Apart from the soil characteristics of the catchment area, the availability of nutrients also depend on the agricultural practices. The Upper Lake of Bhopal , which is known as the life line of the city has a mixed catchment consist both rural as well as urban. The lake receives a large volume of water during monsoon months through number of inlet channels which ultimately increases the nutrients availability in the lake. The present study was, therefore, conducted to assess the impact of the micronutrients on water quality of the lake. The study shows that the area adjoining to Gurabishan khedi have higher concentration of micronutrients than other place.